VISUAL PROGNOSTIC FACTORS IN PATIENTS WITH LENS-INDUCED GLAUCOMA AFTER TREATMENT IN A TERTIARY CARE HOSPITAL (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Lens-induced glaucoma (LIG) is a preventable cause of secondary glaucoma resulting from advanced cataract. Although uncommon in developed countries, it continues to be a significant cause of visual morbidity in countries like India due to delayed presentation and limited awareness regarding timely cataract surgery. Aim: To evaluate the visual prognosis in patients with lens-induced glaucoma following medical and surgical management. Methods: This prospective observational study was conducted at Sree Mookambika Institute of Medical Sciences from May 2025 to March 2026. All diagnosed cases of lens-induced glaucoma were included. Detailed history and comprehensive ophthalmic examination, including visual acuity assessment, slit lamp evaluation, intraocular pressure measurement, gonioscopy, and fundus examination of the fellow eye, were performed. Initial medical therapy was administered to control intraocular pressure and inflammation, followed by cataract extraction. Visual outcomes were assessed using best corrected visual acuity (BCVA) at follow-up. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) version 25.0. Results: At six weeks follow-up, BCVA better than 6/12 was achieved in 33% of patients, 6/18–6/60 in 58%, and less than 6/60 in 9% of cases. Overall, 91% of patients attained BCVA greater than 6/60, indicating satisfactory visual recovery in the majority of cases. Conclusion: Lens-induced glaucoma, though preventable, continues to contribute to visual impairment due to delayed presentation. Early diagnosis, prompt medical management, and timely surgical intervention result in favorable visual outcomes in most patients. Strengthening awareness and accessibility to eye care services is essential to reduce the burden of this condition.